2022
DOI: 10.1002/tqem.21867
|View full text |Cite
|
Sign up to set email alerts
|

Presence of multidrug resistant bacteria in Hurricane Ida overtop sediments in Southeast Louisiana, USA

Abstract: On August 29, 2021, Hurricane Ida made landfall as a category 4 hurricane, bringing a torrent of wind, rain, and storm surge to Southeast Louisiana. This hurricane brought several feet of sediment into the residential areas of southeast Louisiana affecting homes and businesses. The sediment contains industrial waste and sewage sludge. A study was conducted to find the presence of antibiotic-resistant bacteria (ARB) in the sediments. The results of this study show the presence of human polyomavirus BK in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study reported that 96.74% wastewater degradation was observed with ZnTiO 3 nanospheres. Naquin and Boopathy (2022) conducted a study to find the presence of antibiotic-resistant bacteria (ARB) in the sediments after a hurricane event. The sediment also showed high levels of antibiotics such as tetracycline and sulfonamide.…”
Section: There Is a Significant Need For High-performance Catalysts C...mentioning
confidence: 99%
“…The study reported that 96.74% wastewater degradation was observed with ZnTiO 3 nanospheres. Naquin and Boopathy (2022) conducted a study to find the presence of antibiotic-resistant bacteria (ARB) in the sediments after a hurricane event. The sediment also showed high levels of antibiotics such as tetracycline and sulfonamide.…”
Section: There Is a Significant Need For High-performance Catalysts C...mentioning
confidence: 99%